Answer:
f(-2) = -1
f(0) = -5
f(4) = -1
Step-by-step explanation:
The number inside of f( ) is telling you which equation to use to get the answer.
Example:
f(-2) since -2 is less than 0 you would use (x^2) - 5. So, ((-2)^2) - 5 = 4-5 = -1
f(0) since 0 is less than or equal to 0 you would use (x^2) - 5 again. So, ((0)^2) - 5 = 0-5 = -5
f(4) since 4 is grater than 3 you would use (2^(x-1)) - 9. So, (2^(4-1)) - 9 = -1
<u><em>The Graph, try to make it as straight as possible</em></u>
<u><em></em></u>
If the original distance is x, then twice the original distance is 2x.
6 less than something means minus six, or -6.
So the answer would be A) 2x-6
Answer:
A and b
Step-by-step explanation:
Be has an arrow towards the end signaling it moving outward just like GH
Y = -4/5 x - 2
-9 = -4/5 x - 2
-4/5 x = -9 + 2 = -7
-4x = 5(-7) = -35
x = -35/-4 = 35/4
Answer:
-9
Step-by-step explanation: